Analysis of an Epistolary Delirium: Charlotte of Belgium’s “Letters of Madness” - Bénit, André (Thélème. Revista Complutense de Estudios Franceses, 2026)
At the end of July 1867, Charlotte of Belgium, wife of Maximilian of Habsburg, was repatriated to Belgium after spending almost nine months in Miramar, where she had taken refuge following the failure of her mission to Napoleon III and Pius IX, whom she had been unable to convince to continue supporting their empire in Mexico. It was probably in the City of Light and the Eternal City that the first signs of her mental deterioration appeared. Until her death in January 1927, she stayed in Laeken and Tervuren, and then for some fifty years at the castle of Bouchout. On 10 December 1868, she had a strange dream that triggered a leap in her paranoia and led her to write four hundred ‘mad letters’ and ninety notes between February and June 1869, revealing the depths of her thought and the obsessions that tormented her.
Keywords: Charlotte of Belgium; Maximilian; Leopold II; Laeken; Tervuren; Bouchout; letters of madness